Neutralization of Daboxin P activities by rationally designed aptamers. (November 2021) - Devi, Arpita; Doley, Robin
Abstract: Inefficacy and associated risks of current antivenom has raised the need for alternative approaches of snakebite management. Aptamers are one such alternative which is being pursued for therapeutic interventions as well as for design of diagnostic kits due to its high specificity. Present study focussed on designing and validating nucleic acid aptamers against snake venom PLA2, a hydrolytic enzyme present in all venomous snakes. The aptamers were designed by adding nucleic acid chain on the surface of Daboxin P, a major PLA2 enzyme of Daboia russelii venom. Binding characteristics of the aptamers were confirmed by docking to Daboxin P as well as acidic and basic PLA2 s from different snake species using in silico docking. The aptamers folded into different tertiary structures and bound to the active and Ca 2+ binding site of PLA2 enzymes. Molecular dynamics simulation analysis of Daboxin P-aptamer complexes showed that the complexes were stable in an aqueous environment. The electrophoretic mobility shift assay further confirmed the binding of the synthetic aptamers to Daboxin P and other snake venom PLA2 enzymes. The aptamers inhibited the sPLA2 activity with an IC50 value ranging between 0.52 μM and 0.77 μM as well as the anticoagulant activity of Daboxin P. The aptamers could also inhibit the PLA2 activity of Echis carinatus crude venom and anti-coagulant activity of Bungarus caeruleus crude venom, members of big four snakes. However, the aptamers didn't inhibit fibrinogenolytic or proteolytic activity of big four venom as well as the coagulation and hemolytic activities. Thus, aptamers can be rationally designed to inhibit the biochemical and biological activities of snake venom proteins. Highlights: In silico designing of nucleic acid aptamers against Daboxin P. In vitro inhibition of biochemical activities of Daboxin P by the aptamers. In vitro inhibition of some biochemical activities of "Big four" venom.